Dynamics of Ta'buta'an Arts in Kamal Village Arjasa Distric Jember Regency 2006-2020 - Gibson Ireneus Ivander Nua; Kayan Swastika; Bambang Soepeno; Rully Putri Nirmala Puji; Jefri Rieski Triyanto; Guruh Prasetyo (History Education, University of Jember, 2023)
This article discusses the art of Ta'buta'an in the village of Kamal which was originally a means of ritual in the village's cleaning tradition.Research problem: (1) What is the background of the emergence of Ta'buta'an art in Kamal village, (2) What are the dynamics of the elements and functions of the Ta''buta''an art in Kamal Village from 2006 to 2020. The research methods use is Historical methods which include selection, heuristic, criticism, interpretation and historiography. The purpose of this study is to examine the background Ta'buta'an art in Kamal village, Arjasa sub-district, Jember district and Assessing the dynamics of the elements of Ta'buta'an art in Kamal village, sub-district Arjasa Jember Regency from 2006 to 2020. Results of this study show that the background of the Ta'buta'an Tradition comes from the cleaning village ritual which is held routinely every year. Starting from the belief of the people in ancient times there were famines and illnesses. along with the times, the Ta'buta'an tradition has turned into an artistic medium starting in 2006. Ta'buta'an underwent a change from what was originally a ritual tradition to become an artistic means in 2006, then experienced developments in terms of function and elements until 2020. Keywords : Art, Ta’buta’an, Kamal Village, Jember